1999
DOI: 10.1016/s0002-9270(99)00269-5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a new enzyme immunoassay for detecting Helicobacter pylori in feces: a prospective pilot study

Abstract: HpSAT seems to be a reliable method for predicting H. pylori status in anti-H. pylori untreated patients. Conversely, the test appears less suitable to evaluate the outcome of the eradicating treatment. Consequently, it is likely to be accepted for the primary diagnosis of H. pylori status, particularly in dyspeptic young patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 0 publications
1
37
0
Order By: Relevance
“…Although the diagnostic values of fecal testing by HpSA were lower than those of the serological tests, the results in this study were similar to those of other reports using HpSA. [36][37][38][39][40] The sensitivities of the two urine-based tests using frozen urine samples were exceptionally low compared with those of the other tests (Table 2). Therefore, we used Urinelisa to test an additional 436 frozen-stored urine samples from other subjects whose status of H. pylori infection had previously been clarified by serological testing with Immunis anti-pylori.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Although the diagnostic values of fecal testing by HpSA were lower than those of the serological tests, the results in this study were similar to those of other reports using HpSA. [36][37][38][39][40] The sensitivities of the two urine-based tests using frozen urine samples were exceptionally low compared with those of the other tests (Table 2). Therefore, we used Urinelisa to test an additional 436 frozen-stored urine samples from other subjects whose status of H. pylori infection had previously been clarified by serological testing with Immunis anti-pylori.…”
Section: Resultsmentioning
confidence: 96%
“…In contrast, recently developed methods that use urine or stool as samples are totally noninvasive and more convenient than other methods for mass surveys. [33][34][35][38][39][40][41] Several investigators have reported the usefulness of noninvasive tests, including urine-based and fecesbased methods, for the diagnosis of H. pylori infection in patients visiting clinics. [34][35][36][37][38][39][40] Our study of asymptomatic Japanese volunteers also demonstrated the usefulness of the feces-based HpSA test.…”
Section: Discussionmentioning
confidence: 99%
“…Masoero et al [7] found that an overall percentage of contradictory results between UBT and the stool antigen test of 30%, but this discrepancy was significantly higher in treated patients (37%) than in untreated patients (19%). Trevisani et al [8] showed that, in treated subjects, the stool antigen test was positivity associated with negative UBT. The reason is unclear; however, identification of H. pylori coccoid forms was possible by the immunoassay but not by UBT.…”
Section: Discussionmentioning
confidence: 99%
“…The H. pylori stool test is also favorable in young children in whom serology and breath tests may be unreliable or difficult to perform. The superior sensitivity and specificity has been confirmed by many studies which found a pretreatment sensitivity and specificity of 63–100% [17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27]. In a recently published meta-analysis by Gisbert and Pajares [27], 4,769 untreated patients from 43 studies were examined.…”
Section: Hpsa Testmentioning
confidence: 97%
“…The sensitivity, specificity, PPV and NPV were (weighted mean) 88.3 (range 30–100), 92 (range 68–100), 75 and 94.8%, respectively, indicating that the H. pylori stool test is an accurate method of follow-up if performed at least 4 weeks after eradication therapy. Despite these data, several investigators express concern mainly about the specificity of the stool assay in posttreatment testing [18, 28, 29, 30, 31, 32]. In these studies, a considerable percentage of false-positive and (less) false-negative tests were found, and its role in posttreatment assessment was questioned.…”
Section: Hpsa Testmentioning
confidence: 99%